Hardware Implementation of Chaotic Zigzag Map Based Bitwise Dynamical Pseudo Random Number Generator on Field-Programmable Gate Array - Erdem, Ebubekir; Garipcan, Ali Murat (Soc Microelectronics, Electron Components Materials-Midem, 2020)
In this study, successful real-time hardware implementation of discrete-time chaotic zigzag map as a random number generator (RNG) on field-programmable gate array (FPGA) environment is presented. For the hardware modelling of the application, ready-to-use modules defined on 32-bit floating-point numbers and hardware description language (VHDL) are used. In the study, the non-linear dynamic behaviour of the chaotic generator synthesized on the Altera Cyclone IV GX FPGA chip is examined in terms of critical cryptographic competences such as system reliability and statistical randomness quality. The random numbers with poor statistical quality in the system are obtained by passing 32-bit chaotic trajectory outputs through a simple comparison circuit. In order to improve the statistical sufficiency of these numbers, the H function post-processing technique is used. In addition, statistical verification and hardware performance analysis of the generator through NIST 800-22 tests and FPGA chip statistics are presented in the study. The obtained successful results show that the zigzag map can be used in different chaos-based engineering applications, including embedded cryptographic applications. In addition, the low area-energy requirement of PRNG in terms of modelling technique facilitates its practical applicability on resource-restricted applications and architectures.
Strojna implementacija bitnega dinamicnega psevdo-random generatorja števil v FPGA na osnovi kaoticne zigzag karte
Keywords: FPGA; pseudo-random number generator; chaotic zigzag map; H function